2017
DOI: 10.1038/mp.2017.153
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of alcohol consumption and genetic overlap with other health-related traits in UK Biobank (N=112 117)

Abstract: Alcohol consumption has been linked to over 200 diseases and is responsible for over 5% of the global disease burden. Well-known genetic variants in alcohol metabolizing genes, for example, ALDH2 and ADH1B, are strongly associated with alcohol consumption but have limited impact in European populations where they are found at low frequency. We performed a genome-wide association study (GWAS) of self-reported alcohol consumption in 112 117 individuals in the UK Biobank (UKB) sample of white British individuals.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
331
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(358 citation statements)
references
References 65 publications
(84 reference statements)
16
331
2
1
Order By: Relevance
“…Several two-sample MR studies have used summary association data from GWAS that have estimated the effect of genetic variants on the trait of interest conditioned on heritable covariables (e.g. (12)(13)(14)(15)(16)). The use of such GWAS data might have biased the findings of these MR studies for the reasons outlined above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several two-sample MR studies have used summary association data from GWAS that have estimated the effect of genetic variants on the trait of interest conditioned on heritable covariables (e.g. (12)(13)(14)(15)(16)). The use of such GWAS data might have biased the findings of these MR studies for the reasons outlined above.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread use of covariable-adjusted summary associations (e.g. (12)(13)(14)(15)(16)), few considerations have been made about how this could affect the validity of results (e.g. (12-14, 17, 18)), particularly in the context of two-sample MR.…”
Section: Introductionmentioning
confidence: 99%
“…; Clarke et al . ). Further, FGF21 might exert a protective effect during sustained alcohol consumption, since FGF21‐KO mice exhibited more liver damage than WT mice after 16 weeks with 30% ethanol in their drinking water (Desai et al .…”
Section: Introductionmentioning
confidence: 99%
“…49 Across these studies, the most robust association signal for rs1229984 appears to arise from Tolerance, which is notably an index of excessive consumption and consistent with the role of ADH1B in other studies of nonproblem alcohol intake. 50 Plausibly, the strong findings with Desire to cut drinking might also support this as epidemiological studies have shown this criterion to index liability to less severe AD (Table S2 and Figure S7), and therefore, serve as a marker of excessive drinking, rather than severe pathology and impairment. 10,[51][52][53] Differences in associations with other criteria could stem from the relative severity of individual criteria in each dataset or their relationship with excessive drinking.…”
Section: Discussionmentioning
confidence: 81%